Respiratory oscillometry in individuals with fibrodysplasia ossificans progressiva - Anastasiia Vasileva; Joyce K. Y. Wu; Melissa Valaee; Ethan Ortiz; Zoltán Hantos; Lianne Tile; Irene Ho; Angela M. Cheung; Chung-Wai Chow (Orphanet Journal of Rare Diseases)
Abstract Background Fibrodysplasia ossificans progressiva (FOP) is an ultra-rare genetic bone disease that is characterized by progressive heterotopic ossification of the thoracic cavity. Prognosis is poor with cardiopulmonary complications being the main cause of death. Spirometry is a well-established metric of functional exercise capacity and prognosis in lung diseases but its use is limited in this population. Accuracy and validity of spirometry is dependent on forced expiratory maneuvers which are difficult to perform for individuals with FOP. Oscillometry is an effort-independent pulmonary function test that is highly sensitive to changes in respiratory mechanics. Little is known about oscillometry in individuals with FOP. The purpose of this paper is to characterize FOP using oscillometry. Results Eight participants with FOP were recruited for oscillometry prior to spirometry. Cumulative Analogue Joint Involvement Scale (CAJIS) scores were used to evaluate total body and regional FOP burden. Spirometry showed a uniform pattern of restrictive physiology in all eight participants with no significant difference amongst the group. Oscillometry revealed significant diversity in respiratory mechanics and chest wall involvement from normal, airway obstruction and ventilatory inhomogeneity to extra-thoracic airflow obstruction. We compared individuals with normal and abnormal oscillometry and found no statistically significant differences in functional status and clinical parameters. However, there is a tendency for lower CAJIS scores and fewer recent flare-ups in those with more normal respiratory mechanics. The tidal volumes were significantly higher in the group with more normal respiratory mechanics. Two wheelchair-dependent participants exhibited a pattern of high respiratory resistance that increased during both inspiration and expiration, to suggest presence of a fixed extra-thoracic defect. Conclusions Oscillometry provides additional, more detailed information beyond spirometry in individuals with FOP. It is far easier than spirometry to complete and may be useful to help track disease progression and response to therapies in individuals with FOP.